Assessing the impact of optical errors in a novel 2-stage dish concentrator using Monte-Carlo ray-tracing simulation. (August 2018) - Yang, Song; Wang, Jun; Lund, Peter D.; Jiang, Chuan; Liu, Deli
Abstract: Optical errors decrease the performance of solar concentrators. Here we assess the sensitivity of a novel 2-stage dish concentrator against optical errors. We use Monte Carlo ray-tracing, probability statistics, and optical geometrical principles in the analyses. The key finding is that the novel concentrator can reach a high radial distribution of flux concentration and high optical efficiency over a range of optical errors. Compared to a traditional 2-dish concentrator, the performance was clearly better. The results are in good agreement with results from the TracePro ® tool. The results also imply improved tracking stability with the novel 2-stage dish concentrator. Highlights: A novel 2-stage dish concentrator operated in optical error conditions is discussed. An in-house code is edited based on the Monte Carlo method with MATLAB. Comprehensively comparing between the new and conventional concentrators shows the improved optical performance.